2019
DOI: 10.1186/s42409-019-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Portuguese Satisfaction with Family Life Scale

Abstract: The purpose of this study is to examine the psychometric properties of the Satisfaction with Family Life Scale (SWFLS) among Portuguese adolescents. This scale assesses a person's global evaluation of family satisfaction. The participants were 252 high school students from public schools in Lisbon, aged 15-19 years (M = 16.87; SD = 1.21). Confirmatory factor analysis confirmed a one-factor model of the SWFLS among Portuguese adolescents. The SWFLS showed adequate psychometric properties, with good internal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…In particular, family satisfaction correlated positively with both the affective component (i.e., positive affect and positive emotions) and the cognitive component (i.e., life satisfaction) of happiness [ 36 , 37 , 71 , 147 , 148 , 149 , 150 ]. Furthermore, family life satisfaction was positively associated with children’s positive affect [ 148 , 151 , 152 , 153 ] and happiness [ 38 , 126 ], from the perspectives of both children [ 1 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ] and parents [ 27 , 73 , 168 , 169 ]. However, one study reported a non-significant positive correlation between happiness and family satisfaction [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, family satisfaction correlated positively with both the affective component (i.e., positive affect and positive emotions) and the cognitive component (i.e., life satisfaction) of happiness [ 36 , 37 , 71 , 147 , 148 , 149 , 150 ]. Furthermore, family life satisfaction was positively associated with children’s positive affect [ 148 , 151 , 152 , 153 ] and happiness [ 38 , 126 ], from the perspectives of both children [ 1 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ] and parents [ 27 , 73 , 168 , 169 ]. However, one study reported a non-significant positive correlation between happiness and family satisfaction [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study used the SWFLS by Zabriskie and Ward (2013) Although the SWFLS was originally administered to American parents and adolescents from 11-15 years of age, it has also been administered to people between the ages of 26 and 73 (Melton, Ellis, & Zabriskie, 2016) and in different cultural contexts, such as Chilean adolescents and university students . Moreover, the psychometric properties of the SWLFS have been studied in adolescents from many countries, and the results of these studies supported the presence of a single-factor and adequate reliability, with reliability coefficients ranging from .82 to .94 (Caycho-Rodr ıguez et al, 2018;da Costa & Neto, 2019;Zabriskie & Ward, 2013), in agreement with the SWLS from which it is derived (Chinni & Hubley, 2014;Whisman & Judd, 2016). Likewise, prior studies demonstrated that the SWLFS is significantly correlated with family funcioning, family communication, leisuretime activites as a family and other family satisfcation measures (Zabriskie & Ward, 2013), as well as satisfaction with life, self-esteem, perceived social support (da Costa & Neto, 2019) and satisfaction with life related to foods .…”
Section: Introductionmentioning
confidence: 83%
“…These are highly generalized lifestyles in the traditional Peruvian family (Alarc on, 2017). In Portugal, satisfaction with family life is considered one of the main predictors of life satisfaction (da Costa & Neto, 2019;Moreno-Maldonado et al, 2020). The modernization of Portuguese society has generated a series of changes in the structure and functioning of the family, with an increase in the number of families but a decrease in their members, characterized by the presence of only one child.…”
Section: Introductionmentioning
confidence: 99%
“…Cronbach's coefficient alpha calculated in this study was .84. & Neto, 2019;Zabriskie & McCormick, 2003). The answers are evaluated on a 7-point Likert scale from 1 ("Strongly disagree") to 7 ("Strongly agree"), with greater scores expressing greater family life satisfaction.…”
Section: Satisfaction With Life Scale (Swls)mentioning
confidence: 99%